2015
DOI: 10.7314/apjcp.2015.16.8.3111
|View full text |Cite
|
Sign up to set email alerts
|

Changing patterns of Serum CEA and CA199 for Evaluating the Response to First-line Chemotherapy in Patients with Advanced Gastric Adenocarcinoma

Abstract: Background: This study was designed to investigate the value of CEA and CA199 in predicting the treatment response to palliative chemotherapy for advanced gastric cancer. Materials and Methods: We studied 189 patients with advanced gastric cancer who received first-line chemotherapy, measured the serum CEA and CA199 levels,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Several tumor markers, for example, CEA, CA125, CA199 and CA724, are included in community-based cancer screening programs. [6][7][8] It has been reported, however, that not all cases with CRC have elevated tumor indices. This is because the specificity and sensitivity of these tumor markers are not high enough for the precise detection of CRC, leading to low rates of detection and diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Several tumor markers, for example, CEA, CA125, CA199 and CA724, are included in community-based cancer screening programs. [6][7][8] It has been reported, however, that not all cases with CRC have elevated tumor indices. This is because the specificity and sensitivity of these tumor markers are not high enough for the precise detection of CRC, leading to low rates of detection and diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…[911] However, according to the current knowledge, most previous studies on TMs focused on their use as prognostic indicators, predicting the efficacy of both first-line chemotherapy and postsurgical surveillance in GC. [1214] There are few studies on predictive screening or early detection, particularly for CA72-4.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al ( 23 ) found that CA199 ≥14.06 U/mL and CA125 ≥14.30 U/mL were predictors of endometrial carcinogenesis when entered into the risk mode. The variation of CEA and CA19-9 levels in serum can accurately predict the efficacy of first-line chemotherapy in advanced GC ( 24 ). In our research, serum expression levels of PVT1 and CA19-9 showed a correlation in Han GC patients.…”
Section: Discussionmentioning
confidence: 99%